Time domain and frequency domain measurement techniques - Loeb, H. W. (College of Aeronautics, 1969)
The principles underlying two distinct approaches to the measurement of electrical network characteristics over a wide frequency range are outlined, together with brief descriptions of currently available test systems which cover the range 0.1 - 4GHZ. The two techniques are assessed in terms of their ultimate capabilities with regard to accuracy, speed of measurement and costs.